Residues of Endosulfan and Monocrotophos Sprays in Mung Bean [VIGNA Radiata (L.) Wilczek] - Verma, S K; Saxena, R C (Annals of Arid Zone, 2016)
Residues and their dissipation patterns, following the sprays of endosulfan (0.035% and 0.07%) and monocrotophos (0.02% and 0.04%) in the leaves, green pods and grains of mung bean were studied by spectrophotometry. Endosulfan gave initial deposits ((0) of 4.66 to 12.94 ppm on leaves and 1.92 to 2.29 ppm on pods, with half life (RL50) values ranging from 2.67 to 4.64 days on leaves and 1.18 to 1.81 days on pods. Monocrotophos residues on leaves (ID 24.26 to 37.54 ppm) had RL50 of 2.81 to 7.88 days, and on pods (102.34 to 491 ppm) RLso ranged from 4.61 to 6.63 days. Initial deposits were generally high and dissipated faster in summer than in the rainy season but the persi_tence of endosulfan 0.07% spray was belter in summer crop. The dissipation of the insecticides was also faster in green pods. At or after flowering. endosulfan is recommended to be used in the mung bean crop rllised for vegetable purposes, the waiting period being only 1 day. Monocrotophos required a waiting period of 15.22 days. No harvest time residues of enaosulfan were detected in ripe mung bean grains but monocrotophos reSidues could be detected, though below MRL, upto 16 days after spray.